Effects of different types of vegetation cover on soil microorganisms and humus characteristics of soda-saline land in the Songnen Plain - Guo, Liangliang; Tóth, Tibor; Yang, Fan; Wang, Zhichun (Frontiers in Microbiology, 2023)
The prohibition of grazing in the soda-saline grasslands within the Songnen Plain, Jilin Province, China has triggered the succession of various plant communities. This phenomenon has resulted in an augmentation of plant residue input and consequential alterations in soil properties. Up to now, the intricate interplay between the physical and chemical attributes of the soil, the soil microbial community, and their combined influence on soil humus composition remain elusive. Our primary objective was to evaluate the impact of natural vegetation restoration on soil physical, chemical properties as well as microbial community diversity and composition with Miseq at 0 -20 cm soil depth range in soda-saline soil region of Songnen Plain. These soils were covered by dominant soda-saline vegetation species, including: Suaeda glauca Bunge, Puccinellia chinampoensis Ohwi, Chloris virgata Swarta, Phragmites australis (Clay.) Trin Leymus chinensis (Trin.) Tzvelev and bare soil without growing plants were selected for soil physical, chemical properties and community diversity and composition analysis. The soil organic content (SOC) of vegetation restoration soils is greater than that of bare land, and the SOC content under different vegetations varies between 3.64 -11.15 g/kg; In bare land, the changing trend of soil PQ value was basically consistent with the soil organic carbon content. There was a positive correlation observed between SOC content and the relative abundance of Acidobacteria and Mortierella. However, the relative abundance of Actinobacteria, Gemmatimonadetes, and Ascomycota showed a significant negative correlation with SOC. Remarkably, pH was identified as the pivotal factor explaining 11.4% and 12.2% of the variance in soil bacteria and fungi, respectively. Conseqently, pH emerged as the principal driver behind observed microbial dissimilarities. The disparities in SOC composition and content within the soda-saline vegetation can primarily be attributed to the variation in pH. Thus, the reduction of soil pH emerges as a critical step in the process of vegetation restoration in sodasaline land in the future. In summary, the prohibition of grazing holds the potential to augment sodasaline SOC content and enhance microbial diversity. Among the diverse vegetation types studied, Leymus chinensis and Phragmites australis notably exhibited higher SOC carbon content and microbial diversity.